Water resources in England & Wales challenges for the next 10 years : delegate information : Tuesday 26 April 2005. (Thomas Telford, 2005)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 26 April 2005.